Life on top-working@ the Wellcome Trust Centre for Human Genetics: Scotland Yard for DNA detectives. - Ramagopalan, S (2008)
The Wellcome Trust Centre for Human Genetics (WTCHG) was established in 1994 to undertake research into the genetic basis of common diseases. Since June 1999 the centre has been located in the Henry Wellcome Building of Genomic Medicine, University of Oxford. The scientific objective of the centre is to explore all aspects of the genetic susceptibility of disease including the localisation of genes involved in common diseases, characterization of the variants responsible for susceptibility, the understanding of how these DNA variants may contribute to risk of disease in the population and finally, the understanding of how such genetic factors contribute biologically to a disease process. The centre houses multidisciplinary research teams in human genetics, functional genomics, bioinformatics, statistical genetics and structural biology.